2010
DOI: 10.1128/jvi.02202-09
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Generation of Mucosal and Systemic Antigen-Specific CD8+T-Cell Responses following Pulmonary DNA Immunization

Abstract: Although mucosal CD8؉ T-cell responses are important in combating mucosal infections, the generation of such immune responses by vaccination remains problematic. In the present study, we evaluated the ability of plasmid DNA to induce local and systemic antigen-specific CD8 ؉ T-cell responses after pulmonary administration. We show that the pulmonary delivery of plasmid DNA formulated with polyethyleneimine (PEI-DNA) induced robust systemic CD8 ؉ T-cell responses that were comparable in magnitude to those gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
32
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 41 publications
2
32
1
Order By: Relevance
“…Previous studies have shown that intramuscular delivery of PEI-DNA complexes reduced DNA expression from that observed following intramuscular delivery of DNA alone [24,38]. This decrease in DNA expression may explain the reduced immunogenicity of PEI-DNA complexes when delivered by the intramuscular route.…”
mentioning
confidence: 88%
See 3 more Smart Citations
“…Previous studies have shown that intramuscular delivery of PEI-DNA complexes reduced DNA expression from that observed following intramuscular delivery of DNA alone [24,38]. This decrease in DNA expression may explain the reduced immunogenicity of PEI-DNA complexes when delivered by the intramuscular route.…”
mentioning
confidence: 88%
“…PEI is superior to other nonmicrobial transfection agents because of its ability to protect DNA from degradation [18], to escape intracellular endosomal lysis [19] and to efficiently deliver DNA into the nucleus of cells [20]. Formulation with PEI polymers has been employed in DNA-and siRNAbased immunotherapy against cancer [21,22] and in vaccination studies targeting different infectious agents [10,23,24].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…PEI is superior to other non-microbial transfection agents because of its ability to protect DNA from degradation (15), to escape intracellular endosomal lysis, and to efficiently deliver DNA into the cell nucleus (16). Formulation with PEI polymers has been employed in DNA and siRNA (small interfering RNA)-based cancer immunotherapies (17) and in vaccination studies targeting infectious agents (18). In the present study, pVAX1, a Food and Drug Administration-approved plasmid vector, was used as the carrier of G250 DNA, and combined with the synthetic PEI.…”
Section: Introductionmentioning
confidence: 99%